IMMUNE-INFLAMMATORY ISSUES OF RESPIRATORY OCCUPATIONAL PATHOLOGY - Kalmykov, O.O. (World of Medicine and Biology, 2012)
Literature analysis of data concerning immune inflammation in occupational respiratory pathology was performed in the rewiev. While there are many investigations in this field, the problem is too far from its solvation. This predicts futher perspectives of investigations — evaluation of exo- end endogenous mechanisms of inflammation in occupational respiratory pathology.
Keywords: inflammation; occupational pathology; respiratory organs; pathogenesis